Det svenska jordbrukets framtid - Båvius, Henrik; Johansson, Tobias (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
The Common Agricultural Policy the European union´s common agreement about the agriculture financial support. A major change is about to take place in the next 3 years. This reform affects the first 15 members as well as the 10 new members in CAP2. This study contains a future of how agriculture will look like in Sweden in 10 years. The study is mainly based on interviews with key-persons3 in Sweden. The first part describes the CAP-reform in theory, the second part the interviews and the last is a conclusion of the material. The future will see larger farm units. Small farms that do not find their specific niche in production will find themselves in trouble. The ability for Swedish farmers to compete with the rest of Europe is not very high. Sweden does not have perfect weather, or the best conditions for agricultural production. However do some of our landscapes have a comparative advantage in example the "Västerbottens cheese" in the north of Sweden that is known through out the world. The economical situation in Sweden compared to Western Europe is pretty much the same when discussing taxes, but Sweden has differences in the fuel and environment taxes. The CAP-reform was made because of the new members that will join us on the 1st of May, will get stronger in the WTO and lower the prices for the consumers. The changes in the political system of CAP will take about 15-20 years to implement. Sweden has chosen the hybrid model instead of two other economical systems. The Swedish government believe it is the best choice for Sweden. If the Swedish farmers are to stand a chance against this new agricultural political order the government will have to change with it, become more orientated with the market, use innovated thinking and work better together.